Professor Hyun Koo Kim: a great master of single port video-assisted thoracoscopic surgery - You, Scarllet X. (Journal of Thoracic Disease, 2015)
Dr. Kim (Figure 1) is the Associate Professor of Department of Thoracic and Cardiovascular Surgery in Korea University Medical Center. He obtained the PhD. In Medical Science in 2004. He has gained Korean License of Medical Doctor (in 1996), the Korean Board Certification of Thoracic and Cardiovascular Surgery (in 2001) and Korean Board Certification of Critical Care Medicine (in 2009). Dr. Kim is the Director of Korean Society for Nanomedicine and member of lots of professional affiliations, such as Korean Thoracic and Cardiovascular Surgery, Korean Cancer Association, European Association of Cardiothoracic Surgery, International Association for the Study of Lung Cancer, World Molecular Imaging Society (Intraoperative image-guided surgery group), etc. Dr. Kim’s research interest focuses on the thoracic surgery. He has about 30 publications in SCI as first author or corresponding author. He has won the 2012 Merit award of Asian Clinical Oncology Society, and couples of times of Best presentation article in his research field. Dr. Kim has earned the 2012 National Research Foundation of Korea (NRF) grant funded by the Korea government (MEST) and 2012 Korean Health Technology R&D Project, Ministry of Health & Welfare.